טבע דומם עם פנקס ומנורה - בורשטיין דרור (מכאן, 2022)
This article presents a close reading of two interrelated texts about birth: an ancient Talmudic text and a contemporary poem by Naama Shaked. Both feature a description of a fetus in its mother’s womb. However, these descriptions are not just about pregnancy; they are an illustration of the capacity of texts to give birth to other texts across generations, namely the capacity of the consciousness of others, through words, to fertilize another’s consciousness and creativity.